2021
DOI: 10.1021/jacs.1c02687
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Magnetite Nanoparticles Guides Growth from Stabilized Amorphous Ferrihydrite

Abstract: Crystal formation via amorphous precursors is a long-sought-after gateway to engineer nanoparticles with well-controlled size and morphology. Biomineralizing organisms, like magnetotactic bacteria, follow such a nonclassical crystallization pathway to produce magnetite nanoparticles with sophistication unmatched by synthetic efforts at ambient conditions. Here, using in situ small-angle X-ray scattering, we demonstrate how the addition of poly(arginine) in the synthetic formation of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Previous studies investigated the formation process of magnetite and suggested that the process pathway largely depends on the stability of Fe­(III)-bearing intermediates. Intermediates were only detectable when they were stabilized (mainly by additives ), as magnetite was favored when intermediates are unstable . This discrepancy of the magnetite formation pathway coincides with the formation process in this study.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies investigated the formation process of magnetite and suggested that the process pathway largely depends on the stability of Fe­(III)-bearing intermediates. Intermediates were only detectable when they were stabilized (mainly by additives ), as magnetite was favored when intermediates are unstable . This discrepancy of the magnetite formation pathway coincides with the formation process in this study.…”
Section: Resultssupporting
confidence: 84%
“…When the alkali was insufficient, intermediate phases (including GR and Fe­(OH) 3 ) would first form and transform to magnetite gradually within 1 h, approximately, By contrast, magnetite directly precipitates without formation of intermediate phase in the presence of sufficient alkali. A higher concentration of alkali will increase the surface tension and consequently gives rise to the lower free energy barrier. , In addition, surface site blocking is another factor to stabilize these coprecipitated intermediates, given that these nanoparticles had large surface energy and were easily aggregated, inhibiting the subsequent interfacial reaction. Consequently, the coprecipitates of ZnO and Fe-bearing intermediate phase accumulated at the early stage, facilitating Zn 2+ ions diffusion from ZnO to Fe-bearing intermediate phase and consequently enhanced the retention of Zn in magnetite (Figure a,4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that these observations are real and were not generated by specific precipitation conditions or bacterial strain, we performed additional magnetite syntheses with a mixture of Co, Mn, and Zn using distinct protocols and bacterial strain. The choice of metals is made by their frequent use as dopants to tune the magnetic properties of magnetite. ,, First, abiotic magnetite nanoparticles were synthesized using a titration device (see Materials and Methods) following a well-established protocol to produce highly pure magnetite. Using this device, the pH of the precipitation solution is kept constant during magnetite precipitation by adding NaOH solution, and the Fe, Co, Mn, and Zn mixture is progressively added to the precipitation solution. In addition, the magnetotactic strain Magnetospirillum gryphiswaldense MSR-1 was cultivated with a mixture of Co, Mn, and Zn at the same concentration (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] In chemical syntheses, coacervate-directed crystallization was achieved. [24][25][26][27][28] In this work, we used synthetic polycations and polyanions, as well as an aqueous silica source, to investigate bioinspired polymer-induced silicification under mild conditions. We show that each polymer alone stabilizes soluble silicon, whereas polymer mixtures induce silica precipitation.…”
Section: Introductionmentioning
confidence: 99%